Análise da variabilidade dos parâmetros temporais da marcha de idosos com doença de Parkinson durante simulação de travessia de rua - Davi, Juliana Corrêia (2018)
Background: Individuals with Parkinson's disease (PD) have motor symptoms that generally impair gait considerably increasing the risk of falls. During dual tasks, such as at the street crossing, this risk can be even greater. The variability of gait time parameters is considered an important predictor of risk of falls. Objective: To analyze the variability of temporal kinematic variables of gait during simulation of street crossing in patients with PD. Methods: We studied 19 elderly patients with idiopathic PD at an early stage. The evaluation of gait took place on a walkway in three different conditions: gait with preferred speed (Condition 1), gait with simulation of street crossing (Condition 2) and gait with simulation of street crossing in reduced time (Condition 3). For the data collection, the foot switch contact sensor system (Noraxon®) was used. Results: There was no significant difference in the variability between gait conditions for any variable analyzed. Conclusion: Individuals with PD, when subjected to challenging circumstances, such as the street crossing, do not demonstrate significant changes in the variability of the time of step, time of support and time of balance in relation to the march with speed of preference.